Cutaneous Correlates of Metabolic Syndrome and Its Components In Ogbomoso, Nigeria - Adeolu Oladayo Akinboro; Abdulkareem Afolabi Salawu; Olugbenga Edward Ayodele; Olaniyi Emmanuel Onayemi (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Metabolic syndrome (MetS) has been associated with some skin disorders including psoriasis, acne vulgaris, hidradenitis suppurativa, androgenetic alopecia, atopic dermatitis and many others. Although metabolic syndrome is not a dermatological entity, but the increasing isolated reports of its association with cutaneous disorders is a reason for a cross sectional study of this nature. Aim: To examine cutaneous correlates of MetS and its components as defined by National Cholesterol Education Program-Adult Treatment Panel (NCEP ATP) III criteria. Materials and Methods: A cross-sectional study was conducted in which 197 apparently healthy male and non-pregnant female adults attending the General Outpatient Department (GOPD) of Ladoke Akintola University of Technology (LAUTECH) Teaching Hospital, Ogbomoso, Nigeria were included. MetS was diagnosed using NCEP-ATP III criteria and the participants’ skin examined for cutaneous disorders. Univariate and multivariate logistic regression were utilised to demonstrate association between metabolic syndrome, its components and cutaneous disorders. Results: The prevalence of MetS was 32.9%, of which 86.2% of participants were females. Skin disorders associated with MetS reflected the dominance of central obesity on other components. Flat feet (38.5%, p=0.005), and striae (32.3%, p=0.003) were significantly associated with metabolic syndrome in univariate analysis. Abdominal obesity was significantly associated with flat feet (42.7%, p<0.001), achrocordon and varicose veins (18.0% each, p=0.006), striae distensae (31.5%, p<0.001), candida intertrigo and erythrasma (12.4% each, p=0.001). Participants with Striae and flat feet had significant higher mean waist circumference (p<0.001), mean systolic blood pressure (p=0.022 and 0.034 respectively), diastolic blood pressure (p=0.013 and 0.019 respectively) and higher mean BMI (P<0.001). Flat feet was associated with significant higher mean total cholesterol (4.89±1.34 vs. 4.50±1.14, p=0.046) and LDL-c (3.34±1.25vs. 2.86±1.05, p=0.008). In multivariate analysis, the presence of flat feet predicts the odds of metabolic syndrome by 2.2 (95%CI-1.0-4.7, p=0.039) after adjustment of confounders. Conclusion: We demonstrated that flat feet could be an indicator of underlying Metabolic syndrome in obese individuals. Striae distensae, flat feet, and candida intertrigo are significant correlates of abdominal obesity. Obese patients with flat feet are recommended for Metabolic syndrome screenings.